Altered brain spontaneous activity and connectivity network in irritable bowel syndrome patients: A resting-state fMRI study. Issue 6 (June 2015) - Ma, Xiaofen; Li, Shumei; Tian, Junzhang; Jiang, Guihua; Wen, Hua; Wang, Tianyue; Fang, Jin; Zhan, Wenfeng; Xu, Yikai
Highlights: We aimed to provide evidence that brain functional alterations induced by irritable bowel syndrome (IBS) are not limited to local changes but also express at a level of functional integration using resting-state functional magnetic resonance imaging (R-fMRI). IBS patients have decreased amplitude of low-frequency fluctuation (ALFF) in cognitive and pain regulatory and somatosensory regions. Functional connectivity analysis revealed the increased connectivity between cingulate and frontal cortex in the IBS patients. Abstract: Objective: We aimed to provide additional evidence that brain functional alterations induced by IBS are not limited to local changes but also express at a level of functional integration within related brain regions involved in processing of visceral afferent information and somatic pain. Methods: With fMRI data acquired from 21 IBS and healthy control (HC) subjects. We investigated the amplitude of low-frequency fluctuation (ALFF) and region of interest (ROI)-based functional connectivity (FC) to reveal the changes of the brain spontaneous activity and the interaction among different related regions. Results: IBS patients showed decreased ALFF values in the left superior frontal gyrus, right hippocampus, right middle frontal gyrus, bilateral postcentral, and right superior temporal pole, while increased ALFF values in the left median cingulate and left calcarine. There was significant correlation between ALFF values in the altered regions and duration of disease in IBS. FC analysis revealed the increased connectivity between cingulate and frontal cortex in IBS. Conclusions: Our findings could provide both regional and brain connectivity spontaneous neuronal activity properties in IBS. Significance: Our study may lead to a better understanding of intrinsic functional architecture of brain activity in IBS and highlight the potential for using the ALFF and FC metrics as a disease biomarker.